Chemosensitivity of three patient-derived primary cultures of canine pericardial mesothelioma by single-agent and combination treatment - Nabeta, Rina; Kanaya, Ami; Elbadawy, Mohamed; Usui, Tatsuya; Furuya, Tetsuya; Suzuki, Kazuhiko; Uchide, Tsuyoshi (Frontiers in Veterinary Science, 2023)
Introduction Canine mesothelioma is a rare malignant tumor that mostly affects body cavities, such as the pericardial and pleural cavities. Chemotherapy plays a crucial role in the treatment of canine mesotheliomas. We aimed to compare the antitumor effects of single-agent and combination chemotherapeutic agents on patient-derived primary cultures of canine pericardial mesothelioma established in this study. We planned to generate xenograft models for future studies. Material and methods Effusion samples were collected from three dogs with histologically diagnosed pericardial mesothelioma and used for primary culture. Cultured cells were characterized by immunostaining for pan-cytokeratin AE1/AE3, vimentin, Wilms' tumor suppressor gene 1 (WT1), and cytokeratin 5 (CK5). To assess the tumorigenic properties of cells in the effusion and generate a xenograft model, the cell suspension was injected into a severe combined immunodeficient (SCID) mouse either subcutaneously (SC) or intraperitoneally (IP). Lastly, chemosensitivity of established primary cultures against four drugs, doxorubicin, vinorelbine, carboplatin, and gemcitabine, by single-agent treatment as well as combination treatment of carboplatin at a fixed concentration, either 10 or 100 μM, and gemcitabine at different concentrations ranging from 0–1000 μM was assessed by cell viability assay. Results Primary cultures were successfully generated and characterized by dual positivity for AE1/AE3 and vimentin and positive staining for WT-1 and CK5, confirming the mesothelial origin of the cells. In the xenograft models, SC mouse developed a subcutaneous mass, whereas IP mouse developed multiple intraperitoneal nodules. The masses were histopathologically consistent with mesotheliomas. The chemosensitivity assay revealed that carboplatin had the highest anti-tumor effects among the four tested single-agent treatments. Furthermore, carboplatin at 100 μM combined with gemcitabine at clinically relevant doses demonstrated the augmented anti-tumor effects compared to single-agent treatment. Discussion and conclusion Primary cultures and xenograft models generated in this study could be useful tools for in vitro and in vivo studies of canine mesothelioma. Carboplatin is a highly effective chemotherapeutic agent against canine mesothelioma when used as a sole agent and in combination with gemcitabine.